Analisis Bibliometrik Penelitian Pengobatan Herbal Penderita Hipertensi di Indonesia Menggunakan VOS-Viewer - La Ode Alifariki; Sri Susanty; Sukurni Sukurni; Heriviyatno Julika Siagian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the scope of research on the treatment of hypertension with herbs using a bibliometric approach. The method used is to search the database using the Publish-of-Perish application and then extract the search results using the VOS-viewer. The results show that the minimum number of terms associated with using the VOS-viewer is set to 2 times. After being analyzed, 5 clusters (purple, red, green, blue, and orange) show the relationship between one topic and another. VOS-viewer can display bibliometric mappings in three different visualizations: network, overlay, and density. The keywords that appear the most are hypertension, blood pressure, and the elderly. Through the VOS-Viewer, we analyzed how many articles had been published on herbal remedies for people with hypertension and found that marine herbal ingredients had not been used to treat hypertension in Indonesia for that period. In conclusion, this bibliometric approach is essential to determine novelty in conducting further research by identifying basic themes in each study, the field of knowledge, or research that has been carried out so far. Keywords: Bibliometrics, Herbs, Hypertension, Vos-Viewer